Attitude toward eve teasing (Chittagong University Journal of Biological Sciences, 2013)
The present study was conducted to measure the attitude toward eve teasing. For this purpose a scale was developed in Likert format. The scale consisted of 10 statements in Bangla. Based on preliminary scrutinizing and expert judgment for face validity, 29 statements were administered to 100 males and 100 females for items analysis. Of the total 29 statements 10 were found to have significant item total correlation (?= .01 to 0.05) and were retained in the final scale. For measuring reliability of this split half 0.52 and chronbachs alpha 0.56 were computed. This scale was then administered to 200 people (100 males and 100 females) living in different areas of Dhaka city. The obtained data were analyzed by using ANOVA. The data revealed that the interaction effect of gender levels and education was found significant. DOI: http://dx.doi.org/10.3329/cujbs.v6i1-2.17237 The Chittagong Univ. J. B. Sci.,Vol. 6(1&2):107-118, 2011